The Everlasting and the Eternal - Kellenberger, J. author. aut Link
VIII, 188 p.
Keywords: The subject of this book is the relationship and the difference between the temporal everlasting and the atemporal eternal. This book treats the difference between a temporal postmortem life and eternal life. It identifies the conceptual tension in the religious idea of eternal life and offers a resolution of that tension.